NALAR HUKUM ISLAM SATRIA EFFENDI - Akhmad Kasban (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2020)
Abstract Reasoning as a characteristic of philosophy is seen in us}u>l al-fiqh, among Satria Effendi's monumental works are “Ushul Fiqh” and “Problems of Contemporary Islamic Family Law; Jurisprudence Analysis with the Ushuliyah Approach”. The first book shows his position as a drafter, and the second book as a mujtahid with his analysis in a case study. The urgency of knowing the philosophical values ​​of Islamic law is the essence of the purpose of the law itself (maqāsid ash-syari>'`ah).. The results showed that Satria Effendi's method of thinking is a method that uses Baya>ni logic and Burha>ni logic, both methods are applied in: Tajdi>d, Ijtiha>d Maqa>sidi>, Ta`abbudi>-Ta`aqquli>, Ijtiha>d Tat}bi>qi>, Moderation and Preference. While the urgency is: a) Restoring ijtihad textually and contextually; b) Enriching types of Islamic legal thought studies, such as case studies, fiqh manhaji>, muqa>ran fiqh and maqāsid asy-syari>'`ah; c) Forming moderation thinking patterns between liberal and literal; d) Expanding the scope of ijtihad for both istinba>t}i> and tat}bi>qi>; e) Case studies of "jurisprudence analysis" as consideration for subsequent judges, true legal studies, legal synchronization studies of various laws and regulations, and training a sense of justice that must be upheld in society. Keywords: Method of Ijtihad, Contemporary Fiqh, Satria Effendi.